CPWF Annual Report 2005 - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2006)
At this point – just under half way (two years and six months) in the implementation of the first CPWF phase (and three years and eight months since inception began) governance and management processes are running smoothly, it is in reasonable financial health and technical processes – such as issuing new calls and obtaining reviews by our Expert Panel on Scientific Quality – are familiar, although they must be adjusted to each specific instance. The CPWF goal, or impact target, is to contribute to efforts by the global community to ensure that global diversions of water to agriculture are maintained at the level of the year 2000. The intention is that increasing food production will help to achieve internationally adopted targets for decreasing malnourishment and rural poverty by the year 2015, particularly in rural and peri-urban areas in river basins with low average incomes and high physical, economic, or environmental water scarcity or water stress. The program has a specific focus on low income groups within these areas. The objectives of the CPWF are therefore: improvements in agricultural production, sustainability of livelihoods in rural and peri-urban areas; nutrition levels; water quality and maintenance of water related ecosystems services. These positive objectives are complemented by a decrease in agriculture related pollution and water related diseases. (see the CPWF Program Level objective tree on the CPWF website as part of the Medium Term Plan). The CPWF addresses these objectives by contracting research within five thematic areas: crop water productivity; water and people in catchments; aquatic ecosystems and fisheries; integrated basin water management systems; and global and national food and water system. The ‘living laboratories’ for the research are nine river basins across the developing world, being the Indus-Gangetic, Yellow, Sao Francisco, Volta, Limpopo, Nile, Mekong, Karkheh and Andean system of basins.